2021
DOI: 10.1007/s13205-021-02735-6
|View full text |Cite
|
Sign up to set email alerts
|

Nanohybrid electrochemical enzyme sensor for xanthine determination in fish samples

Abstract: An amperometric biosensor for xanthine was designed, based on covalent immobilization of xanthine oxidase (XO) of Bacillus pumilus RL-2d onto a screen-printed multi-walled carbon nanotubes gold nanoparticle-based electrodes (Nano-Au/c-MWCNT). The carboxyl groups at the electrode surface were activated by the use of 1-Ethyl-3-(3-dimethylaminopropyl carbodiimide) (EDC) and N-hydroxysuccinimide (NHS). The working electrode was then coated with 6 μL of xanthine oxidase (0.273 U/mg protein). The cyclic voltammetry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In this study, xanthine oxidase was immobilized on the nanocomposite platform of TiO 2 nanoparticles and MWCNTs. The biosensor showed good linearity for xanthine in the range of 0.5-500 μM with a LOD of 0.5 μM and a response time of 30 s. Sharma et al (2021) Introducing appropriate chemical dopants to metal oxides could regulate the surface electronic state/distribution, improve the electrochemical activity, and regulate the surface chemical affinity. Sahyar et al (2019) developed a novel electrochemical biosensor, which improved the detection performance by adding silver-doped zinc oxide nanoparticles to the conductive polymer structure.…”
Section: Electrochemical Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…In this study, xanthine oxidase was immobilized on the nanocomposite platform of TiO 2 nanoparticles and MWCNTs. The biosensor showed good linearity for xanthine in the range of 0.5-500 μM with a LOD of 0.5 μM and a response time of 30 s. Sharma et al (2021) Introducing appropriate chemical dopants to metal oxides could regulate the surface electronic state/distribution, improve the electrochemical activity, and regulate the surface chemical affinity. Sahyar et al (2019) developed a novel electrochemical biosensor, which improved the detection performance by adding silver-doped zinc oxide nanoparticles to the conductive polymer structure.…”
Section: Electrochemical Methodsmentioning
confidence: 97%
“…The biosensor showed good linearity for xanthine in the range of 0.5–500 μM with a LOD of 0.5 μM and a response time of 30 s. Sharma et al. (2021) designed an amperometric xanthine biosensor by covalent imprinting bacillus RL‐2d xanthine oxidase onto a screen‐printed MWCNTs AuNP‐based electrode. The sensitivity and LOD of the biosensor were 2388.88 μA/cm 2 /nM and 1.14 nM, respectively.…”
Section: Methods For Freshness Assessmentmentioning
confidence: 99%
“…Another study reported an even lower detection limit of 1.14 nM xanthine by covalent immobilization of XOx from Bacillus pumilus RL-2d onto a screen-printed multi-walled carbon nanotubes gold nanoparticle-based electrode (Nano-Au/c-MWCNT). The biosensor was able to detect fish freshness by comparing xanthine levels from fresh fish and 5-day old fish sample [ 108 ]. A summary of analytical performances of various biosensors for the detection of amino acids, biogenic amines and purine derivative compounds is given in Table 6 .…”
Section: Enzyme-based Biosensors For Food Analysismentioning
confidence: 99%
“…This also explains the observed two times higher sensitivity of two-walled CNTs compared with single-walled CNTs and CNTs with up to four walls [ 131 ]. Other recent studies reported the construction of various biosensors based on CNTs as well [ 53 , 104 , 108 ]. Surface functionalization of CNTs with carboxyl groups is an attractive way for increasing hydrophilicity and electronic stability of CNTs.…”
Section: Improvement Strategiesmentioning
confidence: 99%
“…When a fish is sacrificed, the presence of endogenous enzymes in the intestine and the muscle tissues causes the decomposition of nucleotides and other autocatalytic reactions start immediately. , The rapid decomposition of adenosine-5-triphosphate (ATP) into adeonosine-5-di-phosphate (ADP) and further breaks into adenosine-5-monophosphate (AMP), inosine-5-monophosphate (IMP), inosine (I), hypoxanthine (HXn), and xanthine (Xn), respectively. ,, At the time of death, the autolysis causes the rotting of fish by ATP degradation to Xn (3,7-dihydro-purine-2,6-dione), which later ends in the formation of uric acid (UA) by the oxidation of Xn. , The compound IMP majorly contributes toward the taste of the meat, and its degradation to HXn and Xn leads to the bitter taste of the fish meat . The level of chief metabolite Xn in the ATP degradation process in the dead fish increases with the storage time of fish meat .…”
Section: Introductionmentioning
confidence: 99%